2(x-3)=(x+5)

Simple and best practice solution for 2(x-3)=(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)=(x+5) equation:


Simplifying
2(x + -3) = (x + 5)

Reorder the terms:
2(-3 + x) = (x + 5)
(-3 * 2 + x * 2) = (x + 5)
(-6 + 2x) = (x + 5)

Reorder the terms:
-6 + 2x = (5 + x)

Remove parenthesis around (5 + x)
-6 + 2x = 5 + x

Solving
-6 + 2x = 5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + 2x + -1x = 5 + x + -1x

Combine like terms: 2x + -1x = 1x
-6 + 1x = 5 + x + -1x

Combine like terms: x + -1x = 0
-6 + 1x = 5 + 0
-6 + 1x = 5

Add '6' to each side of the equation.
-6 + 6 + 1x = 5 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = 5 + 6
1x = 5 + 6

Combine like terms: 5 + 6 = 11
1x = 11

Divide each side by '1'.
x = 11

Simplifying
x = 11

See similar equations:

| 3(4x+9)-2(7x-12)=81-3x | | 4x+9=4x+45 | | 60x^2+6x=0 | | x(.06)+(.08)(4000-x)=280 | | m^2+m=90 | | 3(8x-4)+2(2x-4)=100 | | 5y+15=14+6+7+y | | 2x+33=5x | | 5y=-7x+24 | | 3x^1=12 | | -2.8+(-6.6)= | | -3x^2+2x=-4 | | 19=0.55x+(0.55)(19) | | 40x+290=15x+75(7x+35) | | 6=t+5s | | X^2+x-1110=0 | | 4(x-5)=2(x+5) | | 2(x+3)+3x=2-(2X+10) | | 516*3x= | | .3x+.8y=(.5)(70) | | 9n-13=4n+7 | | 6=t | | 3x+6x-7=10 | | ((y^2-1)dx)+(xdy)=0 | | 5a-1=a-1 | | c=7.00+0.50x | | (x+2)(x-6)=9 | | 13x-13=7x-7(3x-3) | | 5x-5-x=6x+10+x | | 12(-7)+4=8y | | 27x+9=4x-5x | | a^2x^4+a^2x^2y^2+y^4=0 |

Equations solver categories